PSYCHOLOGICAL ASPECTS OF FOREIGN LANGUAGES: WHY SOME LEARN FAST AND SOME HAVE DIFFICULTY? (Web of Teachers: Inderscience Research, 2025)
Language learning is not only memorizing vocabulary and grammar, but also deeply related to human psychology. Some learners pick up a new language quickly, while others struggle for years. This article examines psychological factors that influence language acquisition, including motivation, fear of making mistakes, memory mechanisms, and age-related differences. In addition, we discuss the benefits of multilingual individuals and practical strategies to improve language learning performance.